Lorentz violation in simple QED processes - Brito, G. P. de; Guaitolini Junior, J. T.; Kroff, D. [UNESP]; Malta, P. C.; Marques, C. (Amer Physical Soc, 2016)
We determine the effect of a CPT-even and Lorentz violating nonminimal coupling on the differential cross sections for some of the most important tree-level processes in QED, namely, Compton and Bhabha scatterings, as well as electron-positron annihilation. Experimental limits constraining the allowed deviation of the differential cross sections relative to pure QED allow us to place upper bounds on the Lorentz violating parameters. A constraint based on the decay rate of parapositronium is also obtained.